INVESTIGATION OF THE RELATIONSHIP BETWEEN MARITAL SATISFACTION AND OCCUPATIONAL BURNOUT LEVELS OF POLICE IN TERMS OF VARIOUS VARIABLES - Safiya YILMAZ DİNÇ (Fırat University, 2019)
The purpose of the study is to investigate the relationship between marital satisfaction and occupational burnout of police. In addition, the study investigate how gender, duration of marriage, economic level variables affects marital satisfaction; how gender, degree level, duration of working time, economic level variables affect occupational burnout of police. The sample of the study consist of an appropriate sample of 315 married police officers and superiors who served in various units of City Police Department in Şırnak, Diyarbakır, Mardin, Iğdır. Maslach Burnout Inventory, developed by Maslach and Johnson (1981) and adapted to Turkish by Ergin (1992), was used in the study to determine occupational burnout levels of Police. In addition, Marriage Life Scale, developed by Tezer (1986), was used to measure the marital satiffaction levels of Police. The data were analyzed with Pearson Product Moment Correlation, t-test, ANOVA, Tukey's multiple comparison test. The results of this study based on relational screening model that burnout was negatively correlated with marriage satisfaction in police officers. It was found that marriage satisfaction of police officers differentiated according to perceived economic level and did not differentiate by gender, duration of marriage. On the other hand, the results of this study demonstrated that burnout levels of police officers differentiated in respect of duration of working time, economic level, degree level and did not differentiate with respect to gender. The results obtained from the research findings are discussed and recommendations are made for future research.